Materials for Energy Infrastructure - Udomkichdecha, Werasak; Mononukul, Anchalee; Böllinghaus, Thomas; Lexow, Jürgen; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2016)
This book presents contributions to the topics of materials for energy infrastructure with a focus on data and informatics for materials. This spectrum of topics has been chosen because challenges in terms of materials are identified to lie in transport and storage of energy, adequate supply of food and water, well-working infrastructure, materials for medical application and health, efficient use of scarce resources or elements and alternate materials solutions as well as recycling. The contributions were invited at the 4th WMRIF Young Materials Scientist Workshop held at the National Institute for Standards and Technology (NIST) in Boulder, Colorado, USA during September 8-10, 2014.  .
Field-based simulations of nanostructured polyelectrolyte gels -- Investigations on the Redox Performance of Pure and Doped CeO2 by Comparing Solid State Reaction and Pechini Synthesis -- Numerical investigations on hydrogen-assisted cracking (HAC) in duplex stainless steels -- Size effect on the Electrodeposited Nickel Investigated by Micro-Compression Test -- Thermoelectric transport from first-principles - Biphenyl-based single-molecule junctions -- Evolution of Fe-intermetallic compounds in the semi-solid state of Al-Mg-Si-Fe alloys --  Imaging ToF-SIMS as a chemical metrology tool to support material and analytical science -- Spinel MnCo2O4 and spinel-nanocarbon hybrids as bifunctional catalysts for alternating oxygen reduction and evolution reactions -- Monte Carlo study of alloy structures in bulk and nanostructured systems -- Microdefects modeling in germanium single crystals -- The influence of temperature and ventilation conditions on combustion products of polymers and on smoke toxicity.  .
Keywords: Materials -- Analysis; Materials; Surfaces (Physics).; Energy storage; Characterization and Analytical Technique; Materials Engineering; Surface and Interface and Thin Film; Mechanical and Thermal Energy Storage